2004
DOI: 10.1111/j.1461-0248.2004.00582.x
|View full text |Cite
|
Sign up to set email alerts
|

Contrary effects of jasmonate treatment of two closely related plant species on attraction of and oviposition by a specialist herbivore

Abstract: Elevated jasmonic acid (JA) concentrations in response to herbivory can induce wounded plants to produce defences against herbivores. In laboratory and field experiments we compared the effects of exogenous JA treatment to two closely related cabbage species on the host-searching and oviposition preference of the diamondback moth (DBM), Plutella xylostella. JA-treated Chinese cabbage (Brassica campestris) was less attractive than untreated Chinese cabbage to ovipositing DBM, while JA-treatment of common cabbag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
37
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 47 publications
1
37
0
Order By: Relevance
“…It has been suggested that correlation between constitutive and induced resistance can be investigated by experiments using a range of wild plants which exhibit low to high degrees of resistance (Lu et al 2004). Up to now, few studies have examined the correlation between the two types of resistance to common herbivores among closely related wild plant species, and trade-oVs between constitutive and induced resistance were detected in some cases (Lewinsohn et al 1991;Litvak and Monson 1998) but not in others (Zangerl and Berenbaum 1990;Thaler and Karban 1997).…”
Section: Electronic Supplementary Materialsmentioning
confidence: 99%
“…It has been suggested that correlation between constitutive and induced resistance can be investigated by experiments using a range of wild plants which exhibit low to high degrees of resistance (Lu et al 2004). Up to now, few studies have examined the correlation between the two types of resistance to common herbivores among closely related wild plant species, and trade-oVs between constitutive and induced resistance were detected in some cases (Lewinsohn et al 1991;Litvak and Monson 1998) but not in others (Zangerl and Berenbaum 1990;Thaler and Karban 1997).…”
Section: Electronic Supplementary Materialsmentioning
confidence: 99%
“…The JA-dependent plant defense is multifaceted; it involves increasing herbivore avoidance and shortening the herbivore's life cycle by decreasing egg production, hatching rates, etc. (Thaler et al, 2001;Lu et al, 2004;Rodriguez-Saona and Thaler, 2005;Abe et al, 2009). It is noteworthy that these facets may also play a part in host suitability for herbivores.…”
Section: Discussionmentioning
confidence: 99%
“…JA-dependent plant defense also has a role in the response and resistance to thrips attack (Abe et al, 2008(Abe et al, , 2009. Interestingly, several reports indicate that application of JA can reduce the feeding, oviposition, and population growth of herbivores (Thaler et al, 2001;Lu et al, 2004;Rodriguez-Saona and Thaler, 2005;Abe et al, 2009). However, the effect of the JA-dependent plant defense on host suitability for herbivores is unknown.…”
mentioning
confidence: 99%
“…Consequently, these plant responses to herbivory have frequently been interpreted as plant defences against further herbivore attack (Karban & Myers, 1989;Karban & Baldwin, 1997;Agrawal & Sherriffs, 2001;Dicke & Baldwin, 2010). However studies have also documented increased herbivore attraction to and oviposition on induced plants (Silva et al, 2012;Rojas, 1999;Landolt, 1993;Lu et al, 2004), highlighting the fact that the ecological function and significance of these induced plant responses remains to be proven (Hare, 2011;Takabayashi & Dicke, 1996). To date, studies on herbivore-induced plant responses have been mostly measured and interpreted from plant mediated effects caused by a single species of herbivore whereas, under natural conditions, plants are often infested and simultaneously fed upon by more than one herbivore species (Thompson, 1998;Strauss, 1991;Vos et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Further adding to the complexity, the current study shows that the responses of one host plant to herbivory had opposing effects on two congeneric insect herbivores. Other studies have shown that multiple host plants have opposing effects on a single insect herbivore species (Silva & Furlong, 2012;Lu et al, 2004). For instance, the diamondback moth (Plutella xylostella) laid more eggs on Jasmonic acid (JA) treated cabbage plants and fewer on JA treated Chinese cabbage, however Pieris rapae did not show such a differential response between JA treated and control cabbage and Chinese cabbage plants (Lu et al, 2004).…”
mentioning
confidence: 99%